2015
DOI: 10.1007/s12600-015-0472-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of non-target effects of Closterocerus chamaeleon (Girault) parasitoid of the eucalypt gall maker Ophelimus maskelli (Ashmead) (Hymenoptera, Eulophidae)

Abstract: The pre-release risk assessment, a recommended practice in biological control programmes, was carried out before introducing Closterocerus chamaeleon (Girault), a eulophid parasitoid of the eucalypt gall maker Ophelimus maskelli (Ashmead) (Hymenoptera, Eulophidae), in Sicily, Italy. We evaluated its host specificity in laboratory small arena no-choice tests on six non-target hosts, using O. maskelli as a control species. The non-target species fit with at least one of the following criteria: a) common geograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 19 publications
0
7
0
2
Order By: Relevance
“…After the first record of P. bliteus in Sicily, its spread all over the region occurred in a short time, showing the high dispersal capacity. Similarly, Closterocerus chamaeleon (Girault), a parasitoid released in Sicily to control the eucalypt gall wasp Ophelimus maskelli (Ashmead) (Hymenoptera, Eulophidae) (RIZZO et al, 2015), rapidly spread through short and long distance dispersal mechanism, being widely distributed in the region after 18 months from its release in 2006(CALECA et al, 2011b.…”
Section: Discussionmentioning
confidence: 99%
“…After the first record of P. bliteus in Sicily, its spread all over the region occurred in a short time, showing the high dispersal capacity. Similarly, Closterocerus chamaeleon (Girault), a parasitoid released in Sicily to control the eucalypt gall wasp Ophelimus maskelli (Ashmead) (Hymenoptera, Eulophidae) (RIZZO et al, 2015), rapidly spread through short and long distance dispersal mechanism, being widely distributed in the region after 18 months from its release in 2006(CALECA et al, 2011b.…”
Section: Discussionmentioning
confidence: 99%
“…This parasitoid is recorded to have parasitised up to 100% of the galls induced by O. maskelli in Sumatra and led to a satisfactory capacity of the leaves to recover after the adult parasitoid emerged from its host (Tavares et al, 2021). Closterocerus chamaeleon individuals with food and no mating permitted showed a greater longevity (21.1 ± 4.1 days, mean ± SD) than those without food and no mating permitted (3.6 ± 0.5 days) and food provided after parasitism (3.8 ± 0.6 days) in a laboratory in Sicily, Italy (Rizzo et al, 2015),…”
Section: Life Cycle Of O Eucalyptimentioning
confidence: 95%
“…Several studies have shown how both gall wasps currently appear to be successfully controlled by various biological control agents, especially hymenopteran parasitoids. Among them, three species were in fact released in Israel for the biological control of O. maskelli: Closterocerus chamaeleon (Girault) (Eulophidae), Stethynium ophelimi Huber and S. breviovipositor Huber (Mymaridae) (MENDEL et al, 2007) and the first one was also released in Italy (LAUDONIA et al, 2006;RIZZO et al, 2006RIZZO et al, , 2015. As regards L. invasa biological control, four species of parasitoids were released in Israel as well: (PROTASOV et al, 2008) but no information is available till now about their presence in Sicily.…”
Section: Hymenoptera Family Eulophidaementioning
confidence: 99%